Barriers and facilitators to retaining a cohort of street-based cisgender female sex workers recruited in Baltimore, Maryland, USA: results from the SAPPHIRE study - Bradley E. Silberzahn; Miles B. Morris; Katelyn E. Riegger; Rebecca Hamilton White; Catherine A. Tomko; Ju Nyeong Park; Katherine H.A. Footer; Steven S. Huettner; Susan G. Sherman (BMC, 2020)
Abstract Background Despite experiencing HIV/STIs, violence, and other morbidities at higher rates than the general public, street-based female sex workers are often absent from public health research and surveillance due to the difficulty and high costs associated with engagement and retention. The current study builds on existing literature by examining barriers and facilitators of retaining a street-based cohort of cisgender female sex workers recruited in a mobile setting in Baltimore, Maryland who participated in the SAPPHIRE study. Participants completed interviews and sexual health testing at baseline, 3-, 6-, 9-, and 12-months. Methods Retention strategies are described and discussed in light of their benefits and challenges. Strategies included collecting several forms of participant contact information, maintaining an extensive field presence by data collectors, conducting social media outreach and public record searches, and providing cash and non-cash incentives. We also calculated raw and adjusted retention proportions at each follow-up period. Lastly, baseline sample characteristics were compared by number of completed visits across demographic, structural vulnerabilities, work environment, and substance use variables using F-tests and Pearson's chi-square tests. Results Although there were drawbacks to each retention strategy, each method was useful in tandem in achieving a successful follow-up rate. While direct forms of contact such as phone calls, social media outreach, and email were useful for retaining more stable participants, less stable participants required extensive field-based efforts such as home and site visits that increase the likelihood of random encounters. Overall, adjusted retention exceeded 70% for the duration of the 12-month study. Participants who were younger, recently experienced homelessness, and injected drugs daily were less likely to have completed all or most follow-up visits. Conclusion Retention of street-based female sex workers required the simultaneous use of diverse retention strategies that were tailored to participant characteristics. With familiarity of the dynamic nature of the study population characteristics, resources can be appropriately allocated to strategies most likely to result in successful retention.